2020
DOI: 10.1111/jre.12753
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine gamma‐lyase aggravates periodontal damage in traumatic occlusion mouse models

Abstract: Background and objective Though impacts of traumatic occlusion (TO) on periodontal tissues and roles of cystathionine γ‐lyase (Cth) gene in the regulation of bone homeostasis have been studied by many, no consensus has been reached so far on whether TO deteriorates the periodontium and precise roles of Cth in occlusal trauma. Therefore, this study aims to investigate the impacts of TO on periodontal tissues and the involvement of Cth gene. Methods Eighty C57BL/6 wild‐type (WT) mice and Cth knockout (Cth−/−) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Similar to the findings for the PDL space, the area of osteonecrosis was larger in the mandible than in the maxilla. After the induction of traumatic hyperocclusion in mice, the number of osteoclasts in alveolar bone at the root furcation was reportedly increased in a time-dependent manner, peaking at 7 days and then decreasing [24,30,33]. Although osteoclast activity is suppressed in humans and mice during N-BP treatment, the number of osteoclasts in ONJ areas is similar to or greater than the number in healthy jaw tissue [8,14,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the findings for the PDL space, the area of osteonecrosis was larger in the mandible than in the maxilla. After the induction of traumatic hyperocclusion in mice, the number of osteoclasts in alveolar bone at the root furcation was reportedly increased in a time-dependent manner, peaking at 7 days and then decreasing [24,30,33]. Although osteoclast activity is suppressed in humans and mice during N-BP treatment, the number of osteoclasts in ONJ areas is similar to or greater than the number in healthy jaw tissue [8,14,34].…”
Section: Discussionmentioning
confidence: 99%
“…Hokugo et al considered that the ONJ-like bone exposure in mice was often associated with food impaction and showed that a gel diet resulted in wound healing with no bone exposure in ZOAtreated mice [31]. Recently, Kozutsumi et al focused on a report that 50% of BRONJ stage 0 (i.e., without bone exposure/necrosis) progressed to a higher stage [32], and created a mouse model of BRONJ stage 0-like lesions to investigate the effect of high-dose BPs on extraction socket healing [33]. In this mouse model, a ZOA dose-dependent increased osteonecrosis in alveolar bone, but overall wound healing was unchanged regardless of ZOA administration.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, traumatic occlusion interferes with the cell viability, fiber alignment, orientation and healing of the PDL. Studies have shown that traumatic occlusion increased PDL width and bone resorption, and reduced bone area by delaying repair [ 55 , 56 ]. Mechanical loading of PDL is essential to preserve the PDL space, improve the regeneration and prevent ankylosis and calcification of the fibers [ 57 , 58 ].…”
Section: Functional Aspects Of Pdl Regenerationmentioning
confidence: 99%
“…Our previous studies found that knockout of Cth gene slowed down the orthodontic tooth movement (OTM; Mo & Hua, 2018) and ameliorated the orthodontic root resorption in mice (Lu et al, 2019). Meanwhile, CTH aggravates periodontal destruction in mouse with traumatic occlusion (Chen et al, 2020). These results indicate the role of CTH in regulating the resorption of periodontal hard tissues.…”
Section: Introductionmentioning
confidence: 99%